Prevention of vaginal and rectal herpes simplex virus type 2 transmission in mice: mechanism of antiviral action - Ceña-Diez, Rafael; Vacas-Córdoba, Enrique; García-Broncano, Pilar; de la Mata, F J; Gómez, Rafael; Maly, Marek; Muñoz-Fernández, M Ángeles (International journal of nanomedicine, 2016)
Topical microbicides to stop sexually transmitted diseases, such as herpes simplex virus type 2 (HSV-2), are urgently needed. The emerging field of nanotechnology offers novel suitable tools for addressing this challenge. Our objective was to study, in vitro and in vivo, antiherpetic effect and antiviral mechanisms of several polyanionic carbosilane dendrimers with anti-HIV-1 activity to establish new potential microbicide candidates against sexually transmitted diseases. Plaque reduction assay on Vero cells proved that G2-S16, G1-S4, and G3-S16 are the dendrimers with the highest inhibitory response against HSV-2 infection. We also demonstrated that our dendrimers inhibit viral infection at the first steps of HSV-2 lifecycle: binding/entry-mediated events. G1-S4 and G3-S16 bind directly on the HSV-2, inactivating it, whereas G2-S16 adheres to host cell-surface proteins. Molecular modeling showed that G1-S4 binds better at binding sites on gB surface than G2-S16. Significantly better binding properties of G1-S4 than G2-S16 were found in an important position for affecting transition of gB trimer from G1-S4 prefusion to final postfusion state and in several positions where G1-S4 could interfere with gB/gH-gL interaction. We demonstrated that these polyanionic carbosilan dendrimers have a synergistic activity with acyclovir and tenofovir against HSV-2, in vitro. Topical vaginal or rectal administration of G1-S4 or G2-S16 prevents HSV-2 transmission in BALB/c mice in values close to 100%. This research represents the first demonstration that transmission of HSV-2 can be blocked by vaginal/rectal application of G1-S4 or G2-S16, providing a step forward to prevent HSV-2 transmission in humans.
Keywords: Chlorocebus aethiops; herpes simplex; Models, Molecular; aplikace rektální; Humans; Herpesvirus 2, Human; Viral Proteins; Dendrimers; silany; Female; Vero buňky; Rectum; lidský herpesvirus 2; Anti-Infective Agents; Herpes Simplex; myši inbrední BALB C; antiinfekční látky; epitelové buňky; lidé; zvířata; molekulární modely; Vagina; polymery; Cercopithecus aethiops; vagina; Polymers; virové proteiny; ženské pohlaví; Epithelial Cells; Male; antivirové látky; Acyclovir; dendrimery; acyklovir; Hydrogen-Ion Concentration; Antiviral Agents; Silanes; tenofovir; Animals; rektum; mužské pohlaví; koncentrace vodíkových iontů; Administration, Rectal; Tenofovir; Mice, Inbred BALB C; Vero Cells